2016
DOI: 10.1002/ajh.24461
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous iron therapy in non‐anemic iron‐deficient menstruating adolescent females with fatigue

Abstract: Menstruating women, with or without underlying bleeding disorders, are at increased risk for developing iron deficiency-related fatigue, even in the absence of anemia. Oral iron therapy has limitations which include poor absorption and non-adherence due to gastrointestinal side effects. We performed a prospective clinical trial of post-menarchal adolescent females with iron-deficiency with or without mild anemia and fatigue who received a standardized regimen of intravenous iron sucrose. The baseline mean (SD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 30 publications
1
31
0
6
Order By: Relevance
“…34 Another recent study also showed improvement in fatigue with iron supplementation to iron-deficient but nonanemic fatigued adolescents. 35 These studies, along with improvements in athletic performance cited previously, clearly demonstrate the role of iron in well-being beyond hemoglobin level.…”
Section: Epidemiology and Etiologiesmentioning
confidence: 84%
“…34 Another recent study also showed improvement in fatigue with iron supplementation to iron-deficient but nonanemic fatigued adolescents. 35 These studies, along with improvements in athletic performance cited previously, clearly demonstrate the role of iron in well-being beyond hemoglobin level.…”
Section: Epidemiology and Etiologiesmentioning
confidence: 84%
“…A randomized double‐blinded placebo‐controlled study demonstrated the efficacy of intravenous iron in nonanemic iron‐deficient premenopausal adult women with fatigue . A smaller single‐arm study of adolescent females with ID and mild/no anemia demonstrated improved fatigue and quality of life after a course of intravenous iron …”
Section: Consultations To the Pediatric Hematology–oncology Specialistmentioning
confidence: 89%
“…La deficiencia de hierro o "ferropenia" representa la deficiencia nutricional más importante a nivel mundial [1][2][3][4] , pero la prevalencia aún no es del todo clara, por falta de estudios que hagan hincapié en esta importante deficiencia; empero algunos autores la sitúan alrededor del 10% a nivel mundial [4][5][6] ; Ortega P. y colaboradores, en un estudio realizado en Venezuela, determinaron que a nivel de América Latina un 10 -30% de mujeres, en edad fértil, cursan con ferropenia1.…”
Section: Introduciónunclassified
“…Ferropenia hace referencia a la insuficiente presencia de hierro en el organismo, sea por disminución en sus reservas o por pérdidas excesivas 4,6 . Para dar con el diagnóstico hay múltiples estudios de laboratorio que podrían ser útiles, empero no todos ellos son costo -efectivos, de hecho, la gran mayoría no lo son; uno muy utilizado es el dosaje de ferritina sérica.…”
Section: Introduciónunclassified
See 1 more Smart Citation